Low voltage series arc fault detection using rogowski coil - Sritrai, Eakburin; Kittiratsatcha, Supat; Polmai, Sompob (My University, 2018)
This paper presents series arc fault detection in low voltage ac circuit using Rogowski coil d/dt sensor. Series arc faults are simulated with various types of loads and current levels to understand the characteristic of arcing signal pattern and level. The Rogowski coil is designed to be able to detect high frequency di/dt component of the arc signal. The experimental results clearly show that by detecting the high frequency component of the di/dt, series arc fault condition can be reliably detected.
Keywords: arc simulator; high-frequency component; low voltage ac; Rogowski coil; series arc fault